Hypoxia Impairs NK Cell Cytotoxicity through SHP-1-Mediated Attenuation of STAT3 and ERK Signaling Pathways - Rui Teng; Yanmeng Wang; Nan Lv; Dan Zhang; Ramone A. Williamson; Lei Lei; Ping Chen; Li Lei; Baiyan Wang; Jiaqi Fu; Xuna Liu; Aili He; et al. (Journal of Immunology Research)
Natural killer (NK) cells are innate immune effectors with potent antitumor activity. However, tumor cells can create an immunosuppressive microenvironment to escape immune surveillance. Although accumulating evidence indicates that microenvironmental hypoxia plays an important role in favoring tumor development and immune evasion, it remains unclear by what means hypoxia directly impairs NK cell antitumor activity. In this study, we confirmed that hypoxic NK cells showed significantly lower cytotoxicity against tumor cells. Consistent with this finding, we found that the reduction in NK cell cytotoxicity resulting from hypoxia correlated to the lower expression of granzyme B, IFN-γ, and degranulation marker CD107a, as well as activating receptors including NKp30, NKp46, and NKG2D expressed on the surface of NK cells. More importantly, we further demonstrated that a reduction in the phosphorylation levels of ERK and STAT3 secondary to hypoxia was strongly associated with the attenuated NK cell cytotoxicity. Focusing on the mechanism responsible for reduced phosphorylation levels of ERK and STAT3, we reveal that the activation of protein tyrosine phosphatase SHP-1 (Src homology region 2 domain-containing phosphatase-1) following hypoxia might play an essential role in this process. By knocking down SHP-1 or blocking its activity using a specific inhibitor TPI-1, we were able to partially restore NK cell cytotoxicity under hypoxia. Taken together, we demonstrate that hypoxia could impair NK cell cytotoxicity by decreasing the phosphorylation levels of ERK and STAT3 in a SHP-1-dependent manner. Therefore, targeting SHP-1 could provide an approach to enhance NK cell-based tumor immunotherapy.